RETRACTED: Pengungkapan identitas sosial melalui bahasa dalam nama diri keluarga Jawa Islam tiga generasi: kajian sosiosemantik - Agnes Adhani; Priska Meilasari (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
RETRACTION TO:Adhani, A., & Meilasari, P. (2025). Pengungkapan identitas sosial melalui bahasa dalam nama diri keluarga Jawa Islam tiga generasi: Kajian sosiosemantik. Jurnal Penelitian Pendidikan Indonesia, 11(2), 250–258. https://doi.org/10.29210/020254073This article has been retracted by Publisher based on the following reason:The article titled “Pengungkapan Identitas Sosial Melalui Bahasa dalam Nama Diri Keluarga Jawa Islam Tiga Generasi: Kajian Sosiosemantik” has been retracted at the request of the editorial board. Although the manuscript had been formally accepted for publication, it still required minor revisions during the post-acceptance editing stage. However, the authors refused to make the necessary corrections, citing time constraints and formally requested withdrawal of the article. This conduct violates the ethical standards established by the Committee on Publication Ethics (COPE), which state that authors have a responsibility to engage constructively with the editorial process, including fulfilling revision obligations after acceptance. COPE further emphasizes that withdrawal of accepted articles without valid and justified reasons undermines the integrity of the peer-review system and misuses editorial resources. Therefore, to maintain transparency and uphold publication ethics, the editorial board has decided to retract the article.